Maternal mortality : report of meeting held at Friends' House. Euston Road on November 15, 1932 (London : Maternal Mortality Committee)
1932-11 1932 1930s 36 pages It is quite natural that this should be so, because children are inspected by the School Medical Officer, employed people are subject to Health and Unemployment Insurance, and so we have a record of the amount of sickness which they endure. But the married women who are not employed, we have no general record at all as to the amount of sickness among them. The facts have never been collected, and so, in spite of what the Minister said about the impossibility of indulging in large, expensive new schemes of inquiry, I would venture to suggest that where sickness is concerned, true economy lies in preventive measures. We cannot prevent sickness unless we know its cause, so that there is a case for a really wide and close inquiry into the whole problem of the health of married women, showing the extent to which their ill-health, when it does exist, is due to specific causes, whether it is due to childbirth, to the lack of care connected with childbirth, or to any other cause. I have great pleasure in supporting the resolution. THE COUNTESS OF SELBORNE (President of the Hants. County Nursing Association) : Ladies and gentlemen, the Minister rather congratulated the nation on the progress that had been made in dealing with Maternal Mortality and said that the Report from the Committee which had been inquiring into it was already bearing fruit. Well, I should prefer to call it a flower which we hope some day will develop into a fruit, but until the rate of mortality goes down, I don't think there is any fruit worth gathering. The death-rate of Holland is 3.3 per 1,000 births. The death-rate of England and Wales is 4.3 per 1,000 births, but the death-rate of those women who are nursed by Queen Victoria's Jubilee nurses is 2. That is really a very remarkable figure because those nurses deal with the poorest in the country. They don't nurse well-to-do persons except perhaps in some very remote country district where no other nurses are available. All people who can afford it like to have their own nurse to look after them when they are laid up with a baby, and the Queen's Nurses only do district nursing and go round from case to case. Therefore, they really are only employed by those who cannot afford any other, and yet they have lower figures than not only England and Wales, but than Holland, and you must remember that they take responsibility for all their abnormal cases that are treated by doctors. If an abnormal case is being nursed by a Queen's Nurse and she has to send for a doctor and the woman dies in the doctor's hands, she is written down as one of the deaths that occur among the patients of the Queen's Nurses so that practically the advantage they have in figures over England and Wales must be obtained in the normal cases. It is in the normal cases that the care they give is so much (19) 292/824/1/45